(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2011)
High school teachers, particularly those who teach history and/or social studies, subjects where issues of civic concern are central, have an increasingly complex “explicit pedagogical responsibility for promoting their students’ social, moral and emotional growth”. This is especially so given changed national and global realities post-9/11, ncluding the concomitant swell of ongoing controversy in the U.S. vis-a-vis the meaning and implications of patriotism. In their efforts to facilitate “constructive and meaningful” citizenship education experiences – specifically, experiences that foster a long-term sense of efficacy and purpose with regard to active civic engagement – history and/or social studies teachers invariably confront complex pedagogical and curriculum challenges in their work with high school students. Concomitantly, this approach to teaching demands complex pedagogical skills; because teachers who aim to foster students’ social-emotional, moral, and civic learning inevitably face complex teaching dilemmas. Such dilemmas often mirror complex systemic challenges. In this paper, I explore what the demands of this process mean to/for teachers, specifically in terms of their personal and professional development. The following overarching questions have guided my inquiry: How do history/social studies teachers describe and make sense of constructive controversy as a way to promote adolescent students’ social-emotional, ethical, civic and academic learning? What does this teaching and learning process demand of teachers, particularly in terms of their own cognitive, social and emotional competencies?